Fiber optic reference guide : a practical guide to communications technology - Goff, David R. (Focal Press, 2013)
The Fiber Optic Reference Guide offers readers a solid understanding of the principles of fiber optic technology, especially as it relates to telecommunications, from its early days to developing future trends. Using a minimum of jargon and a wealth of illustrations, this book provides the underlying principles of fiber optics as well as essential practical applications. The third edition is updated to include expanded sections on light emitters, semiconductor optical amplifiers, Bragg gratings, and more systems design considerations. Fiber optics plays a key role.